Mechanisms underlying glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1 secretion. (14th March 2016) - Reimann, Frank; Gribble, Fiona M
Abstract: The incretin hormones, glucose‐dependent insulinotropic peptide and glucagon‐like peptide‐1, are secreted from intestinal K‐ and L cells, respectively, with the former being most abundant in the proximal small intestine, whereas the latter increase in number towards the distal gut. Although an overlap between K‐ and L cells can be observed immunohistochemically or in murine models expressing fluorescent markers under the control of the two hormone promoters, the majority (>80%) of labeled cells seems to produce only one of these hormones. Transcriptomic analysis showed a close relationship between small intestinal K‐ and L cells, and glucose sensing mechanisms appear similar in both cell types with a predominant role of electrogenic glucose uptake through sodium‐coupled glucose transporter 1. Similarly, both cell types produce the long‐chain fatty acid sensing G‐protein‐coupled receptors, FFAR1 (GPR40) and FFAR4 (GPR120), but differ in the expression/functionality of other lipid sensing receptors. GPR119 and FFAR2/3, for example, have clearly documented roles in glucagon‐like peptide‐1 secretion, whereas agonists for the endocannabinoid receptor type 1 have been found to show largely selective inhibition of glucose‐dependent insulinotropic peptide secretion. In conclusion, although K‐ and L cell populations overlap and share key molecular nutrient‐sensing mechanisms, subtle differences between the responsiveness of the different cell types might be exploited to differentially modulate glucose‐dependent insulinotropic peptide or glucagon‐like peptide‐1 secretion. Abstract : This Minireview compares and to some degree contrast signalling mechanisms underlying glucose dependent insulinotropic polypeptide and glucagon‐like peptide‐1 secretion from K‐ and L‐cells.